Fostering Constitutional Equality: Unveiling the Implementation of Legal Aid for Underprivileged Citizens in Karimun Regency - Ibsam, Rifqi; Nurlaily, Nurlaily; Seroja, Triana Dewi (Nurani Hukum, 2023)
The provision of legal aid is a manifestation of  access to law and justice for the poor provided by the state under the mandate of the Constitution of the Republic of Indonesia. Especially in Karimun Regency, there is a disparity between the number of poor people and the number of legal aid organizations. This study aims to find out, first, the application of legal aid for the poor in the perspective of the constitutional rights of Karimun Regency citizens and second, how to optimize  the provision of legal aid for the poor in Karimun Regency. This research uses normative-empirical legal research methods with legal, conceptual and case approaches. Data sources come from primary and skunder data. The results showed: First, the implementation of legal aid for the poor in Karimun Regency has not been implemented optimally. This happens because of various problems or factors including, 1) the absence of legal aid regulations to the poor in the form of regional regulations; 2) Legal Aid Providers Do Not Work optimally; 3) The unbalanced number of Legal Aid Providers and Legal Aid recipients; and 4) Lack of legal knowledge and awareness for the poor. Second, to optimize the application of legal aid to the poor in Karimun Regency can be done through several stages including, 1) Regional Regulations related to legal aid are immediately ratified; 2) Supervision and Strict Sanctions Against Legal Aid Providers for the Implementation of Legal Aid; and 4) The addition of Legal Aid Organizations (OBH) in Karimun Regency verified by the Ministry of Law and Human Rights.